The cerebrospinal fluid immune cell landscape in animal models of multiple sclerosis - Wu, Gregory F. (Frontiers in Molecular Neuroscience, 2023)
The fluid compartment surrounding the central nervous system (CNS) is a unique source of immune cells capable of reflecting the pathophysiology of neurologic diseases. While human clinical and experimental studies often employ cerebrospinal fluid (CSF) analysis, assessment of CSF in animal models of disease are wholly uncommon, particularly in examining the cellular component. Barriers to routine assessment of CSF in animal models of multiple sclerosis (MS) include limited sample volume, blood contamination, and lack of feasible longitudinal approaches. The few studies characterizing CSF immune cells in animal models of MS are largely outdated, but recent work employing transcriptomics have been used to explore new concepts in CNS inflammation and MS. Absence of extensive CSF data from rodent and other systems has curbed the overall impact of experimental models of MS. Future approaches, including examination of CSF myeloid subsets, single cell transcriptomics incorporating antigen receptor sequencing, and use of diverse animal models, may serve to overcome current limitations and provide critical insights into the pathogenesis of, and therapeutic developments for, MS.